T Cells and Adoptive Immunotherapy: Recent Developments and Future Prospects in Gastrointestinal Oncology - Amedeo Amedei; Elena Niccolai; Mario M. D'Elios (Clinical and Developmental Immunology)
Gastrointestinal oncology is one of the foremost causes of death: the gastric cancer accounts for 10.4% of cancer deaths worldwide, the pancreatic cancer for 6%, and finally, the colorectal cancer for 9% of all cancer-related deaths. For all these gastrointestinal cancers, surgical tumor resection remains the primary curative treatment, but the overall 5-year survival rate remains poor, ranging between 20–25%; the addition of combined modality strategies (pre- or postoperative chemoradiotherapy or perioperative chemotherapy) results in 5-year survival rates of only 30–35%. Therefore, many investigators believe that the potential for making significant progress lies on understanding and exploiting the molecular biology of gastrointestinal tumors to investigate new therapeutic strategies such as specific immunotherapy. In this paper we will focus on recent knowledge concerning the role of T cells and the use of T adoptive immunotherapy in the treatment of gastrointestinal cancers.